Optimization of Mucilage Removal from Cress Seeds (L. sativum) - Hilal İşleroğlu; İzzet Türker (Journal of Advanced Research in Natural and Applied Sciences)
In this study, optimum removal conditions of the cress seed mucilage by a chemical method were deter-mined. Moreover, proximate analysis (moisture, fat, protein, ash and total carbohydrate) of the cress seed was carried out. The independent process variables were sodium bicarbonate concentration (0-0.5 M), solvent-to-seeds ratio (25-75 ml/g) and soaking time (3-9 hours). A central composite design having 24 points for given independent variables was used and the optimization of the process conditions was done by desirability function approach. The results showed that proximate analysis results of the cress seed were in accordance with the previous reports in literature, and fat and protein percentage was found to be higher than 20%. The mucilage removal study results showed that higher concentrations of sodium bicar-bonate enhanced the mucilage removal. Also, higher soaking times increased the solubility of the seed coat polysaccharides of the cress seeds, resulting in better mucilage removal. The optimum chemical mucilage removal conditions were determined as 0.43 M sodium bicarbonate, solvent-to-seeds ratio of 75 ml/g and 8.96 hours of soaking time. At these conditions, total carbohydrate (determined using Anthrone method) in the final extract was predicted as 2.47 g/ml. Verification tests were carried out at the optimum conditions and there was no statistical difference between experimental (2.64±0.43 mg/ml) and predicted values.